In Vitro Propagation and Cryopreservation of Lady's Slipper Orchid (Paphiopedilum niveum (Rchb.f.) Stein) - Sutthinut Soonthornkalump (2019)
Thesis (Ph.D., Biology)--Prince of Songkla University, 2019